(untitled) - Clayton, Keith N (Columbus, Ohio, 1984)
This manual, planned, to accompany an introduction to statistics, includes suggested test items arranged by chapter. It should be obvious that severral different items select carefully to avoid some content, and instructors need to,...
Keywords: Statistics